2023
DOI: 10.1186/s12979-023-00327-x
|View full text |Cite
|
Sign up to set email alerts
|

Frailty impacts immune responses to Moderna COVID-19 mRNA vaccine in older adults

Abstract: Background Immune responses to COVID-19 mRNA vaccines have not been well characterized in frail older adults. We postulated that frailty is associated with impaired antibody and cellular mRNA vaccine responses. Methods We followed older adults in a retirement facility with longitudinal clinical and serological samples from the first Moderna mRNA-1273 vaccine dose starting in February 2021 through their 3rd (booster) vaccine dose. Outcomes were anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Others have also found differences in SARS-CoV-2-specific antibody quantities across age groups, and together this supports the implementation of separate vaccination schedules for more highrisk groups such as the elderly, to boost protective IgG and Bmem levels. [89][90][91][92] The third COVID-19 vaccine dose has been shown to significantly boost NAb levels against Omicron, regardless of the primary vaccine formulation. 93 It will be of interest to also examine RBD-specific Bmem recognition of VoC after booster doses, as these memory cells will likely be the source of these increased NAb titers.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also found differences in SARS-CoV-2-specific antibody quantities across age groups, and together this supports the implementation of separate vaccination schedules for more highrisk groups such as the elderly, to boost protective IgG and Bmem levels. [89][90][91][92] The third COVID-19 vaccine dose has been shown to significantly boost NAb levels against Omicron, regardless of the primary vaccine formulation. 93 It will be of interest to also examine RBD-specific Bmem recognition of VoC after booster doses, as these memory cells will likely be the source of these increased NAb titers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not find any influence of frailty on anti-RBD IgG or nAb levels but this is limited by the absence of severely frail participants in the studied population. Nonetheless, another study indicated that the booster vaccination appeared to overcome the effects of frailty on spike and RBD protein antibody quantity for severely frail individuals 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The decay in antibodies and MBCs observed in our cohorts of nursing home residents may be attributed to immunosenescence [ 41 ]. Published studies have also indicated frailty, defined as a complex phenomenon due to a cumulative decline in multiple physiologic systems resulting in reduced resistance to stressors, as an explanation for decreased post-vaccine antibody response [ 6 , 42 , 43 ], where higher levels of frailty result in decreased SARS-CoV-2 antibody responses, similar to what has been observed following the receipt of other viral vaccines (e.g., Zoster [ 44 ]). A study by Shapiro et al indicated that immune response to a third dose of mRNA COVID-19 vaccine booster dose appears to overcome reduced immunity associated with frailty [ 45 ], consistent with our findings, based on linear mixed modeling, indicating reduced decay rates after multiple spike exposures.…”
Section: Discussionmentioning
confidence: 95%